2022
DOI: 10.1002/pam.22403
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Monthly Poverty Rates in the United States

Abstract: Official poverty estimates for the United States are presented annually, based on a family unit's annual resources, and reported with a considerable lag. This study introduces a framework to produce monthly estimates of the Supplemental Poverty Measure and official poverty measure, based on a family unit's monthly income, and with a two‐week lag. We argue that a shorter accounting period and more timely estimates of poverty better account for intra‐year income volatility and better inform the public of current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 54 publications
0
45
0
Order By: Relevance
“…Counterintuitively, we observed that COVID-19-related increases in income were associated with a greater prevalence of financial hardship, food insecurity, and poor self-rated health when compared with no changes in income. It is possible these participants had received their first COVID-19 stimulus check, hazard pay, or the increased unemployment insurance benefit, which were disproportionately allocated to lower income workers and workers in blue- and pink-collar frontline and/or essential jobs ( Kinder & Stateler, 2021 ; Parolin et al, 2022 ), who are more likely to experience financial hardship generally. Our observed associations between intersecting group identity and reported income increases support this theory as most subgroups generally reported more exposure to income increases relative to White men with higher education, with the exception of Latinx men and women with ≤HS who were disproportionately barred from relief efforts ( Gonzalez et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Counterintuitively, we observed that COVID-19-related increases in income were associated with a greater prevalence of financial hardship, food insecurity, and poor self-rated health when compared with no changes in income. It is possible these participants had received their first COVID-19 stimulus check, hazard pay, or the increased unemployment insurance benefit, which were disproportionately allocated to lower income workers and workers in blue- and pink-collar frontline and/or essential jobs ( Kinder & Stateler, 2021 ; Parolin et al, 2022 ), who are more likely to experience financial hardship generally. Our observed associations between intersecting group identity and reported income increases support this theory as most subgroups generally reported more exposure to income increases relative to White men with higher education, with the exception of Latinx men and women with ≤HS who were disproportionately barred from relief efforts ( Gonzalez et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Working‐age adults and children are expected to be most affected by poverty, which has risen in the COVID‐19 crisis. [ 31 , 32 ] Researchers have reported that experiencing economic hardship during the COVID‐19 period increases the sense of distress and danger, and that people who are already poor will be more affected by this crisis. In our study, students who experienced economic difficulties also stated that their home environment was inadequate for participating in distance education (Table 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…14 We can see in Appendix Figure 1 It is also worth asking if the large changes from one month to the next that we see for child poverty rates from the CPSP measure are plausibly capturing large changes in child wellbeing. The comparisons to well-being measures from the Census Household Pulse Survey in Parolin et al (2022) indicate an association between the monthly poverty measures and wellbeing measures at the state/month level that is stronger in the simulations that account for policy changes than with poverty measures that do not account for any transfer or a measure of nonemployment. 15 However, this is a fairly weak test given that the alternative poverty measures do not incorporate the trillions of dollars in cash transfers paid out over this period, and nonemployment is a poor proxy for poverty.…”
Section: Changes In Real-time Poverty and The Advance Child Tax Creditmentioning
confidence: 98%
“…Parolin et al 2022 for more details). The CPSP measure also includes in its income measure predicted values of key COVID-related income transfers such as the Economic Impact Payments and expanded unemployment insurance benefits using information on potential eligibility status as well as the distribution schedules of these payments (seeParolin et al 2020 and Bitler et al 2020).Parolin et al then compare this predicted monthly income measure to one-twelfth of the SPM threshold provided in the ASEC files for each SPM unit to determine the monthly poverty status of each individual in the CSP ASEC.The CPS-ASEC is released on an annual basis.…”
mentioning
confidence: 99%
See 1 more Smart Citation